2011
DOI: 10.1007/s11262-011-0593-9
|View full text |Cite
|
Sign up to set email alerts
|

Three clusters of bovine kobuvirus isolated in Korea, 2008–2010

Abstract: Fecal samples (n = 107) were collected from cattle with ascertained or suspected diarrheal disease on Korean farms during 2008-2010. Of these, 37 samples tested positive for bovine kobuvirus. The 37 positive samples came from 32 cattle that exhibited diarrhea and five cattle that were non-diarrhetic. The majority of the virus-positive feces samples were from calves under 1 month of age (n = 25). Nine of the 37 cattle infected with bovine kobuvirus were confirmed to have a co-infection with other viruses includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 12 publications
6
30
0
Order By: Relevance
“…Among 3 BKV-positive calves with diarrhea, 2 were <1 month of age and 1 was ≈5 months of age. Previous studies reported high prevalence of BKV infection in young calves with diarrhea; 20.9% (38/182) in calves <2 months of age in Brazil and 26.7% (23/86) in calves <1 month of age in South Korea (5,9). Our study further supports the hypothesis that BKV causes neonatal diarrhea in calves.…”
Section: Research Letterssupporting
confidence: 88%
See 1 more Smart Citation
“…Among 3 BKV-positive calves with diarrhea, 2 were <1 month of age and 1 was ≈5 months of age. Previous studies reported high prevalence of BKV infection in young calves with diarrhea; 20.9% (38/182) in calves <2 months of age in Brazil and 26.7% (23/86) in calves <1 month of age in South Korea (5,9). Our study further supports the hypothesis that BKV causes neonatal diarrhea in calves.…”
Section: Research Letterssupporting
confidence: 88%
“…Leyi (1). Since then, BKV has been reported in Thailand, Hungary, the Netherlands, Korea, Italy, Brazil, China, and Egypt (2)(3)(4)(5)(6)(7)(8)(9). However, circulation of BKV in North America remains unclear.…”
Section: Research Lettersmentioning
confidence: 99%
“…The cDNA was synthesized using the instructions (TaKaRa Bio Inc.) and then stored at −20°C. BKoV was detected by an RT-PCR assay targeting a 631 bp fragment of the 3D gene according to previous report (Jeoung et al, 2011). To screen for the presence of co-infections with bovine rotavirus (BRV), bovine coronavirus (BCoV), and bovine viral diarrhea virus (BVDV), all the BKoVpositive diarrheic samples were subjected to specific RT-PCR assays for these viruses (Guo et al, 2019;Zheng et al, 2014).…”
mentioning
confidence: 99%
“…Based on the inspection of the tree and according to the pairwise homology and distance analyses, the strains 50R/IT, 51R/IT, 61R/IT and 71R/IT segregated with the CKVs (bootstrap value, 99 %) within the novel proposed species Aichivirus D [9]. All of the BKV-like sequences obtained in this study clustered along with the prototype strain U1 and the BKVs previously detected either in diarrhoeic or asymptomatic calves [2,3,5,12,17].…”
mentioning
confidence: 66%
“…Upon sequence analysis of 3D fragments, nine strains (92B/IT, 67R/IT, 70R/IT, 45R/IT, 43R/IT, 37R/IT, 35R/IT, 95R/IT, 106R/IT) shared 93.7-99.4 % nt sequence identity with each other and displayed the closest relatedness (91.2-97.4 % nt sequence identity) to the prototype BKV strain U1 [17] and to several BKV-like sequences identified in cattle in Korea and in the Netherlands [2,5,6,12], while they were more distantly related (89.3-91.0 %) to strains previously detected in Italy [3]. For one strain, sample 50R/ IT, the highest sequence identity was found to the newly described CKVs [8,9].…”
mentioning
confidence: 98%